2017
DOI: 10.1155/2017/6037159
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Systematic Elimination of a Targeted Chromosome in Human Cells

Abstract: Embryonic trisomy leads to abortion or congenital genetic disorders in humans. The most common autosomal chromosome abnormalities are trisomy of chromosomes 13, 18, and 21. Although alteration of gene dosage is thought to contribute to disorders caused by extra copies of chromosomes, genes associated with specific disease phenotypes remain unclear. To generate a normal cell from a trisomic cell as a means of etiological analysis or candidate therapy for trisomy syndromes, we developed a system to eliminate a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…LoxP sites are frequently co-integrated with a gene encoding a fluorescent protein to facilitate FACS-based enrichment of cells with the desired karyotype (Matsumura et al 2007 ; Otsuji et al 2008 ; Zhu et al 2010 ; Sato et al 2017 ; Thomas et al 2018 ; Wakita et al 2022 ). Alternatively, co-integration of loxP with, for instance, the herpes simplex virus thymidine kinase gene (HSV-tk) allows for the negative selection of cells with an integration in the chromosome of interest (Sato et al 2017 ; Wakita et al 2022 ). Mammalian cells expressing HSV-tk are killed by the anti-viral drug Ganciclovir (GCV) (Borrelli et al 1988 ), and thus only cells that have eliminated the chromosome with the integrated HSV-tk gene can survive this treatment.…”
Section: Methods To Eliminate Specific Chromosomesmentioning
confidence: 99%
“…LoxP sites are frequently co-integrated with a gene encoding a fluorescent protein to facilitate FACS-based enrichment of cells with the desired karyotype (Matsumura et al 2007 ; Otsuji et al 2008 ; Zhu et al 2010 ; Sato et al 2017 ; Thomas et al 2018 ; Wakita et al 2022 ). Alternatively, co-integration of loxP with, for instance, the herpes simplex virus thymidine kinase gene (HSV-tk) allows for the negative selection of cells with an integration in the chromosome of interest (Sato et al 2017 ; Wakita et al 2022 ). Mammalian cells expressing HSV-tk are killed by the anti-viral drug Ganciclovir (GCV) (Borrelli et al 1988 ), and thus only cells that have eliminated the chromosome with the integrated HSV-tk gene can survive this treatment.…”
Section: Methods To Eliminate Specific Chromosomesmentioning
confidence: 99%
“…The Cas9 target site on HSF2BP intron 3 (5′-GAGATTGCCTATCGTAGAGTGGGNGG-3′) is located 10 kb downstream of the Penta-D STR locus. In addition, we constructed a “chromosome elimination cassette” (2797 bp) containing a CAG promoter-driven puromycin-delta thymidine kinase (puroΔTK) flanked by inverted loxP sites to bear positive/negative drug selection markers [ 36 , 37 ] (using puroΔTK fragment from Addgene #84036). The targeting vector (6451 bp DNA plasmid) designed with homology arms against HSF2BP intron 3 (973 and 982 bp in length) (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies using genetic engineering have revealed the possibility of performing aneuploidy therapy in cultured cells. Here, we summarize some of the main studies aimed at eliminating an entire chromosome using the Cre/loxP system [79][80][81][82][83][84][85], the TKneo transgene for positive and negative antibiotic selection [86], CRISPR/Cas9 system-mediated multiple cleavage [87,88], and zinc finger nuclease (ZFN)-mediated knock-in of the XIST gene to silence one copy of chromosome 21 [89] (cited in Table 2).…”
Section: Gene Targeting-mediated Chromosome Eliminationmentioning
confidence: 99%
“…A single loxP site contains two 13-bp inverted repeats flanking an asymmetric 8-bp core sequence recognized by Cre recombinase [90]. Integration of the inverted loxP into the chromosomes were performed by conventional gene targeting, CRISPR/Cas9 nickase system, and TALEN technology, respectively [82,83,91]. Chromosomes with inverted loxP sites can be converted to unstable dicentric and acentric chromosomes in a Cre recombinase-dependent manner (Figure 1).…”
Section: Cre/loxp System-mediated Chromosome Eliminationmentioning
confidence: 99%
See 1 more Smart Citation